1999
DOI: 10.1074/jbc.274.50.35933
|View full text |Cite
|
Sign up to set email alerts
|

Vinexin Forms a Signaling Complex with Sos and Modulates Epidermal Growth Factor-induced c-Jun N-terminal Kinase/Stress-activated Protein Kinase Activities

Abstract: Vinexin, a novel protein that plays a key role in cell spreading and cytoskeletal organization, contains three SH3 domains and binds to vinculin through its first and second SH3 domains. We show here that the third SH3 domain binds to Sos, a guanine nucleotide exchange factor for Ras and Rac, both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 48 publications
2
63
0
Order By: Relevance
“…However, it is possible that the ␤-catenin⅐lp-dlg⅐vinexin complex can link cadherin to actin cytoskeleton through vinexin binding to vinculin and contribute to the formation of cell-cell contacts. Alternatively, ␤-catenin⅐lp-dlg complex might compete with the vinexin binding to Sos, a guanine nucleotide exchange factor for Ras and Rac, and modulate the signaling, because both Sos and lp-dlg bind to the third SH3 domain of vinexin ␤ (14). Further studies are necessary to examine these possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it is possible that the ␤-catenin⅐lp-dlg⅐vinexin complex can link cadherin to actin cytoskeleton through vinexin binding to vinculin and contribute to the formation of cell-cell contacts. Alternatively, ␤-catenin⅐lp-dlg complex might compete with the vinexin binding to Sos, a guanine nucleotide exchange factor for Ras and Rac, and modulate the signaling, because both Sos and lp-dlg bind to the third SH3 domain of vinexin ␤ (14). Further studies are necessary to examine these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…To define the lp-dlg binding site of vinexin ␤, a deletion mutant containing only the third SH3 domain was excised from plasmids of GST-3rdSH3 (14) and subcloned into pGBT9. Deletion mutants containing the second and third SH3 (amino acids 120 -328) and the linker (amino acids 173-271) region of mouse vinexin ␤ were amplified by polymerase chain reaction and subcloned into pGBT9.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that expression of vinexin ␣ affected the actin cytoskeletal organization in NIH3T3 cells, and that expression of vinexin ␤ promoted the spreading of C2C12 cells (18). Moreover, vinexin ␤ regulates the EGF-induced activation of JNK and the anchoragedependent activation of ERK2 induced by EGF (20,21). Furthermore, it was reported that vinexin interacted with scaffold attachment factor B2 or estrogen receptor, both of which are implicated in the response to steroid hormone (22,23).…”
mentioning
confidence: 99%